What Is the Optimal Management of Patients With Prior Septic Arthritis of the Ankle Who Are Undergoing Total Ankle Arthroplasty (TAA)?. (July 2019) - Winters, Brian; Da Rin de Lorenzo, Ferdinando; O'Neil, Jake
Recommendation: There is a paucity of data regarding total ankle arthroplasty (TAA) in patients with prior infection involving the ankle, whether it be septic arthritis, osteomyelitis, or infection of the surrounding soft tissues. We recommend that patients with prior infections in the affected ankle be worked up for infection, including a thorough history and physical examination, as well as ordering serologic tests and possible aspiration of the joint. During ankle arthroplasty in patients with prior infection, antibiotics should be added to the cement (if used), and the joint should be thoroughly cleansed. Intraoperative cultures of bone and soft tissue should also be obtained. Level of Evidence: Consensus. Delegate Vote: Agree: 100%, Disagree: 0%, Abstain: 0% (Unanimous, Strongest Consensus)